Two dimensional alveolar ridge augmentation using particulate hydroxyapatite and collagen membrane: A case report - Aparna Singh; Anika Daing; Vishal Anand; Jaya Dixit (Elsevier, 2014)
Background: Ridge augmentation procedures require bone regeneration outside of the existing bony walls or housing and are therefore often considered to be the most challenging surgical procedures. The bony deficiencies can be managed with GBR techniques involving bone grafting material and membrane while vertical augmentation may require the use of space-creating support mechanisms. Non-degradable membranes have been used for ridge augmentation with encouraging results however; requirement of second surgery for its removal and associated infection on exposure may compromise the desired results. These problems can be overcome by employing resorbable collagen membranes. Different bone graft materials are also used in combination with resorbable membranes, for prevention of membrane collapse and maintenance of space, as they lack sufficient rigidity. Particulate hydroxyapatite bone graft may be better alternative, because it treats the underlying bone defect to restore the natural support of the tissue architecture. Moreover, its use avoids potential donor site complications associated with autogenous block grafts. Method: Patient described in this report presented with missing right maxillary incisor with ridge deficiency. A treatment approach involving localised ridge augmentation with particulate hydroxyapatite and collagen membrane was used. Result: Six month post-operative periapical radiograph demonstrated a significant vertical bone fill. Conclusion: The clinical and radiographic findings of the present case suggests that HA in conjunction with a resorbable collagen membrane may be an acceptable alternative to the autogenous block graft and non-resorbable membrane in the treatment of compromised alveolar ridge deficiencies.